1997
DOI: 10.1063/1.365859
|View full text |Cite
|
Sign up to set email alerts
|

Persistent photoconductivity in n-type GaN

Abstract: Results of photoconductivity measurements in undoped n-type and Se-doped GaN epitaxial thin films are presented. Similar to the photoluminescence spectra, the photoconductivity also shows a broad yellow band centered around 2.2 eV. It is found that persistent photoconductivity (PPC) does exist in all the studied thin films. In addition, the PPC effects can be observed for the pumping photon energy down to the yellow band. The results reveal that the origin of the PPC effect and yellow luminescence may arise fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(47 citation statements)
references
References 21 publications
4
43
0
Order By: Relevance
“…When carriers are trapped, the surface potential changes and the escape of the trapped carriers are delayed. The defects inside the InP NWs in our devices may be similar to those reported by Chen et al for GaN thin film [313]. The high lattice mismatch (∼8.1%) between InP and Si causes dislocation defects at the InP/Si heterointerface [52].…”
Section: Surface Traps Passivation and Persistent Photoconductivitysupporting
confidence: 71%
See 1 more Smart Citation
“…When carriers are trapped, the surface potential changes and the escape of the trapped carriers are delayed. The defects inside the InP NWs in our devices may be similar to those reported by Chen et al for GaN thin film [313]. The high lattice mismatch (∼8.1%) between InP and Si causes dislocation defects at the InP/Si heterointerface [52].…”
Section: Surface Traps Passivation and Persistent Photoconductivitysupporting
confidence: 71%
“…Both bulk defects, such as vacancies, impurities, and surface states can collectively contribute to the long trapping of photogenerated excess carriers and manifest as a temporary boost in dark conductivity, which may exist for days or even years [316]. PPC studies have been reported for some structures, e.g., GaN thin films [311], [313], [314], [317]- [320], InGaN epitaxial films [315], GaNNWs [321], and InP NWs [322].…”
Section: Surface Traps Passivation and Persistent Photoconductivitymentioning
confidence: 99%
“…Photoconductive GaN detectors [2][3][4][5][6][7][8][9][10][11][12][13][14] have early attracted much interest because of their simplicity and high responsivity. Although Khan et al reported a fast and linear photoconductor with a visible rejection of more than four decades, 2 most of the groups working on these devices describe persistent photoconductivity (PPC) effects, [3][4][5][6][7][8][9][10][11][12][13] that is, the photoinduced increase in the conductivity persists for a long time after the light is removed.…”
Section: Introductionmentioning
confidence: 99%
“…The yellow-band luminescence (YL) and persistent photoconductivity (PPC) have also been observed and extensively investigated in undoped and doped GaN. 8,9 A recent report claimed that PPC and YL in GaN are related to each other through defects associated with a broad deep level. 10 The origins of YL and PPC are still in debate.…”
mentioning
confidence: 99%
“…10 The origins of YL and PPC are still in debate. [8][9][10][11] In this work, a variety of undoped GaN with electron densities on the order of mid-10 16 cm -3 and with a Hall mobility varying from < 50 cm 2 /sV to > 500 cm 2 /sV at room temperature were investigated using temperature variable Hall effect measurements. The objective was to better understand what limits the Hall mobility of undoped GaN as well as its relationship with the PPC effect.…”
mentioning
confidence: 99%